Biological-chemical treatment of polycyclic aromatic hydrocarbon contaminated soil / Salina Alias - XAlias, Salina Alias (Institute of Graduate Studies, UiTM, 2016)
Industrialization has caused a great deal of environmental pollutions such as soil contamination via deposition and spillage of contaminants. One of the major contaminants is high molecular weight (HMW) polycyclic aromatic hydrocarbon (PAH), specifically the benzo(a) pyrene. Benzo(a)pyrene is known for its carcinogenic effect. Several soil remediation strategies have been proposed. However, to date, remediation of benzo(a)pyrene contaminated soil using zero-valent iron (ZVI) and hybrid bacteria-ZVI has not been investigated. The capability of bacteria, namely, Corynebacterium urealyticum and Sphingobacterium spiritovorum to degrade benzo(a)pyrene in soil were firstly investigated in three conditions, single, binary and ternary substrate experiments. Binary and ternary substrate experiments involved the degradation of benzo(a)pyrene, a HMW-PAH with the presence of low molecular weight (LMW) PAH. It was found that both bacteria were capable of degrading the benzo(a)pyrene in the presence of anthracene and phenanthrene (both are LMW-PAHs). However the degree of degradation varied. For instance, the degradation of benzo(a)pyrene was enhanced with the presence of anthracene and phenanthrene in ternary substrate experiment, where 30% of benzo(a)pyrene was degraded. In the single and binary substrate experiment which only phenanthrene was present, about 24% and 14% of benzo(a)pyrene was degraded. Both bacteria degraded the benzo(a) pyrene at the rate of 1.508 – 3.229 mg/kg/day…